Pyriproxyfen influences growth as well as thyroid hormone–related and gh/ igf-1 gene expression during the early life stage of zebrafish (danio rerio) - Horie, Yoshifumi; Mitsunaga, Kensuke; Chee, Kong Yap (Elsevier BV, 2023)
Pyriproxyfen is an agricultural chemical pesticide that has been detected in the aquatic environment. This study aimed to clarify the effects of pyriproxyfen on the growth as well as thyroid hormone– and growth-related gene expression of zebrafish (Danio rerio) during its early life stage. Pyriproxyfen exhibited a lethal effect in a concentration-dependent manner: the lowest and no effect concentrations were 250.7 and 111.7 μg/L, respectively. These concentrations were considerably higher than the residual environmental concentrations, indicating the low risk of this pesticide when present at such concentrations. In the zebrafish group treated with 56.6 μg/L pyriproxyfen, thyroid hormone receptor β gene expression levels remained unchanged, whereas thyroidstimulating hormone β subunit, iodtyronin deiodinase 2, and thyroid hormone receptor α gene expression levels significantly decreased compared with the control group expression levels. In zebrafish treated with 111.7 or 250.7 μg/L pyriproxyfen, iodtyronin deiodinase 1 gene expression levels significantly increased. These results indicate that pyriproxyfen disrupts thyroid hormone activity in zebrafish. Furthermore, pyriproxyfen exposure inhibited zebrafish growth; consequently, we examined the expression of growth hormone (gh) and insulin-like growth factor-I (igf-1), which are important for growth. Pyriproxyfen exposure suppressed gh expression; however, the igf-1 expression levels remained unchanged. Therefore, growth inhibition due to pyriproxyfen exposure was attributed to the suppression of gh expression.